2022
DOI: 10.1302/0301-620x.104b7.bjj-2021-1806.r1
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable and non-modifiable risk factors in hip fracture mortality in Norway, 2014 to 2018

Abstract: Aims This study aimed to identify risk factors (patient, healthcare system, and socioeconomic) for mortality after hip fractures and estimate their relative importance. Further, we aimed to elucidate mortality and survival patterns following fractures and the duration of excess mortality. Methods Data on 37,394 hip fractures in the Norwegian Hip Fracture Register from January 2014 to December 2018 were linked to data from the Norwegian Patient Registry, Statistics Norway, and characteristics of acute care hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…An English report found a 30-day mortality risk of 1.2% during 2009-10 [25]. Like us, some of these more recent studies reported a higher 30-day mortality risk in males compared with females between 2010 and 2017 [11,24,26], while others found that male was not significant predictor in 2014 [20]. In the present study, the 30-day mortality decreased significantly from 2010 to 2020, despite an increase over time in the mean age of patients and their comorbidities.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…An English report found a 30-day mortality risk of 1.2% during 2009-10 [25]. Like us, some of these more recent studies reported a higher 30-day mortality risk in males compared with females between 2010 and 2017 [11,24,26], while others found that male was not significant predictor in 2014 [20]. In the present study, the 30-day mortality decreased significantly from 2010 to 2020, despite an increase over time in the mean age of patients and their comorbidities.…”
Section: Discussionsupporting
confidence: 53%
“…The 1-year mortality is high over time in the literature, with risks about 29% in the 1960s [3], 23% in the 1980s [29], and 26% in the 1990s [7,28]. In the most recent studies, no significant changes in the last 20 years have been reported with risks maintained about 22% [2,6,11]. Like us, the most common predictors reported were male, age > 80 years, and Charlson index > 2 [30].…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations